A comparative study of proximate compositions, phytochemical constituents, and anti-nutritional contents of pulps and seeds of Garcinia buchananii fruit - Zeneba Kadir Abdisa; Kumsa Negasa Andersa; Abebe Yimer Tadesse; Endris Hussen Ahmed; Tolcha Techane Alemu; Hayat Hassen Mohammed (Heliyon)
Garcinia buchananii is a tropical wild edible plant that is locally consumed in the Southern Nations, Nationalities, and Peoples Regional state of Ethiopia. However, there is limited information comparing nutritional, phytochemical, and anti-nutritional factors present in fruit pulps and seeds of the fruit. Therefore, this study aimed to investigate and compare the proximate compositions, phytochemical constituents, and anti-nutritional contents of the fruit pulp and seeds. Data analysis was conducted using SPSS software version 20. The proximate analysis revealed that the pulp had higher moisture content (80.52 %) compared to the seed (42.4 %), whereas the seed contained more crude protein, crude fat, crude fiber and carbohydrate. However, the phytochemical constituents were relatively more abundant in the pulp compared to the seed. The pulp exhibited higher levels of total phenolic content (31.62 %), total flavonoid content (22.27 %), ascorbic acid (0.67 %), and inhibition percentage (15.31 %), but was lower in beta-carotene (4.60 %). The fruit seed has higher anti-nutritional values than the pulp. Overall, the pulp and seeds of the Garcinia buchananii fruit are nutrient-rich and can be used in food product development and formulation. Being high in moisture content and low in anti-nutritients the pup of the plant can be utilized in the form of juice.